Comparison Between Effects of Four Crystalloid Solutions on Acid-Base and Electrolyte Abnormalities in Stranded Juvenile Loggerhead Sea Turtles (Caretta caretta) - Inurria, Alicia; Santana, Ángelo; Casal, Ana B.; Calabuig, Pascual; Suárez-Pérez, Alejandro; Orós, Jorge (Frontiers in Veterinary Science, 2022)
Dehydration, electrolyte abnormalities, and acid-base alterations are common findings in stranded sea turtles. Fluid therapy is essential for reestablishment of homeostasis. The aim of this study was to compare the efficacy and effects on acid-base and electrolyte status of four different crystalloids (0.9% NaCl solution, 0.9% NaCl and lactated Ringer’s solutions 1:1 ratio, Plasmalyte, and Jarchow’s solution) in 63 stranded juvenile loggerhead turtles (Caretta caretta). Crystalloid fluids were administered intracoelomically on the day of admission for a duration of three consecutive days at a rate of 20 mL/kg/day through the inguinal fossa. Blood samples were collected at three timepoints: on admission, 24 h after discontinuing fluid therapy and prior to release. Samples were analyzed using a portable electronic blood analyzer for pH, pCO2, pO2, bicarbonate, lactate, sodium, potassium, chloride, glucose, and BUN concentration. Thirty-four loggerhead turtles (53.9%) had some type of acid-base alteration at the time of admission. The combination of 0.9% NaCl and lactated Ringer’s solutions resulted in the highest percentage of improved/resolved acid-base and electrolyte abnormalities (33.4 % more animals with normal acid-base status compared to the admission time) compared to Jarchow’s solution, which was the least effective (15.8% decrease in the number of animals with normal acid-base status compared to the admission time). This study constitutes the second controlled study of fluid therapy in sea turtles, and corroborates the recommendation made previously on the use of 0.9% NaCl + lactated Ringer solution to resolve mild to moderate acid-base alterations in juvenile loggerhead turtles. In addition, convalescent acid-base, electrolyte and plasma biochemical reference intervals are also provided as a standard profile for sea turtle rehabilitation centers.